Ultrasound of the pediatric upper gastrointestinal tract. - Cohen, H. L. (1989)
Fluid aided ultrasound examination of the neonatal upper gastrointestinal tract has been highly successful in the evaluation of hypertrophic pyloric stenosis. It can diagnose midgut volvulus. It has proved helpful in triaging significant gastroesophageal reflux. We have used this technique in evaluation of malrotation and in the diagnosis of duodenal atresias and stenoses. Its usefulness will be properly assessed by further investigation and diagnostic experience. If it merely saves radiation when used as a triaging tool, it serves a significant purpose. If it can prove a primary diagnostic modality, patients can only benefit.